Denaturing gradient-gel electrophoresis screening of familial defective apolipoprotein B-100 in a mixed Asian cohort: Two cases of arginine3500 → tryptophan mutation associated with a unique haplotype - Choong, M.-L. (2014)
Clinical Chemistry